(untitled) (Development Service Industry Management, 2025)
The relevance of the research is determined by global instability, rapid technological development, economic turbulence, and increasing competition, which intensify the need for effective resource management, particularly time. Time management is no longer merely a tool for personal productivity but has transformed into an integral element of strategic business planning. Under conditions of uncertainty, the timeliness of managerial decisions, flexible adaptation to changes, and clear planning become critical for business survival and growth. Digital time management tools — specialized software, mobile applications, project management systems, and integrated planners — significantly expand business opportunities in planning, monitoring, and coordinating activities, thereby enhancing productivity, transparency of task execution, and team discipline. The problem lies in the fact that traditional approaches to planning often fail to meet the challenges of the digital era. The insufficient study of the effectiveness of digital time management tools in business planning complicates strategy formation, reduces managerial efficiency, and increases risks. Therefore, an important task is to justify the feasibility of integrating digital solutions into organizational management systems and to develop practical recommendations for their implementation. The purpose of this research is to determine the significance and effectiveness of digital time management tools in business planning under uncertainty. The objectives focus on analyzing contemporary challenges, exploring the functional capabilities of digital solutions, evaluating their advantages and limitations, and formulating recommendations for optimizing the use of time and resources. The findings demonstrate that digital tools such as Trello, Notion, ClickUp, Todoist, and others provide opportunities for task organization, progress monitoring, routine process automation, and integration with business systems. Their implementation helps optimize time allocation, improve productivity, strengthen teamwork, and ensure rapid responses to environmental changes. At the same time, effectiveness depends on adapting these tools to the specifics of a company and the digital literacy of employees. It is concluded that digital time management tools represent a strategic resource that enhances business resilience and competitiveness in unstable conditions. Their integration into business planning reduces risks, improves decision-making processes, and allows the concentration of resources on achieving priority goals.